Efforts to Increase Youth Awareness of Environmental Cleanliness and Creativity in Tebing Tanjung Selamat Village, Padang Tualang District, Langkat Regency - Nasution, Lita; Kemal, Isthifa; Prayogi, Muhammad Andi; Alfarizi, Roni (Universitas Negeri Medan, 2023)
This service activity aims to increase the basicity of youth and increase creativity in protecting the environment. The method of implementing youth service activities to form characters who care about the surrounding environment and support the field of creativity in Tebing Tanjung Selamat Village, Kec. Tualang Field. The program requires physical and mental readiness, as well as knowledge and skill readiness. With this service activity, the relationship between higher education institutions as a source of knowledge and the community is getting better so that handling in various fields of development will be integrated.